The Process of Practicum Supervision on Guidance and Counselling Teachers in Primary School: A Case Study - Nor, Mohd Zarawi Mat (EDUCARE, 2016)
ABSTRACT: Since the roles of supervisor are important in order to produce professional counsellorsâ knowledge, attitudes, and skills, TTI (Teachers Training Institute) is suggested to revise its qualifications of its lecturers. Generally, practicum supervision process is a vital component in any profession, including guidance and counselling field. This qualitative case study aimed at exploring the process of practicum supervision of guidance and counselling teachers in Primary School in ITE (Institute of Teacher Education) in Malaysia. There were 28 participants participating in the study: 7 lecturers and 21 supervisees. A total of 21 in-depth interviews and 7 FGD (Focus Group Discussions) were carried out in data collection process and later were analysed manually based on the N-Vivo programme procedure. The results have shown that one theme, three sub-themes, and four categories were emerged. The theme is procedure of management and structuring of practicum supervision of guidance and counselling teachers in Primary School; sub-themes are prior supervision phase, current supervision phase, and post-supervision phase. The categories are structure and contract of supervision, contextual orientation, types of supervision, methods of supervision, evaluation, and conclusion contract. Peer checker, member checks, Cohen-Kappa index, and audit trail techniques have been applied in order to seek validity and reliability of the data. Impact of the study and recommendations are also discussed.Â KEY WORDS: Practicum Supervision; Guidance and Counselling; Teachers in Primary School; Teachers Training Institute; Professional Counsellors.About the Author: Dr. Mohd Zarawi Mat Nor is a Senior Lecturer at the Department of Medical Education, School of Medical Sciences USM (Science University of Malaysia), 16150 Kubang Kerian, Kelantan, Malaysia. For academic interests, the author is able to be searched via his e-mail at: zarawi@usm.myHow to cite this article? Nor, Mohd Zarawi Mat. (2016). âThe Process of Practicum Supervision on Guidance and Counselling Teachers in Primary School: A Case Studyâ in EDUCARE: International Journal for Educational Studies, Vol.9(1), August, pp.1-12. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Chronicle of the article: Accepted (March 11, 2016); Revised (May 20, 2016); and Published (August 30, 2016).